Supplemental Substrate Enhancement of 2,4-Dinitrophenol Mineralization by a Bacterial Consortium - Hess, T. F. (1990)
A Janthinobacterium sp. and an actinomycete, both capable of mineralizing 2,4-dinitrophenol (DNP), were used to construct a consortium to mineralize DNP in nonaxenic bench-scale sequencing batch reactors (SBRs). Average K(m) values for DNP mineralization by pure cultures of the Janthinobacterium sp. and the actinomycete were 0.01 and 0.13 μg/ml, respectively, and the average maximum specific growth rate (μ(max)) values for them were 0.06 and 0.23/h, respectively. In the presence of NH(4)Cl, nitrite accumulation in pure culture experiments and in the SBRs was stoichiometric to initial DNP concentration and the addition of nitrogen enhanced DNP mineralization in the SBRs. Mineralization of 10 μg of DNP per ml was further enhanced in SBRs by the addition of glucose at concentrations of 100 and 500 μg/ml but not at 10 μg/ml. Possible mechanisms for this enhanced DNP mineralization in SBRs were suggested by kinetic analyses and biomass measurements. Average μ(max) values for DNP mineralization in the presence of 0, 10, 100, and 500 μg of glucose per ml were 0.33, 0.13, 0.42, and 0.59/h, respectively. In addition, there was greater standing biomass in reactors amended with glucose. At steady-state operation, all SBRs contained heterogeneous microbial communities but only one organism, an actinomycete, that was capable of mineralizing DNP. This research demonstrates the usefulness of supplemental substrates for enhancing the degradation of toxic chemicals in bioreactors that contain heterogeneous microbial communities.